2024
DOI: 10.3389/or.2023.11866
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Cancer Patients in Asia: Challenges and Countermeasures

Yu Wang,
Xinqing Zhang,
Yilin Huang
et al.

Abstract: With the increasing incidence of cancer worldwide, palliative care has become an effective intervention to relieve cancer patients’ pain and improve their quality of life, although the present development of palliative medicine and hospice care in many Asian countries remains insufficient. To this end, this review comprehensively discussed the main challenges that influence the promotion of palliative medicine, from the perspective of both healthcare professionals and cancer patients. We further proposed and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Nevertheless, other studies suggested different RT doses and segmentations played various immunomodulatory role ( 87 ). Some scholars considered low-dose RT, which is commonly used for patients with metastatic diseases as palliative care ( 91 , 92 ), can better induce anti-tumor immune activation at the molecular level, reshape TIME, and improve the infiltration and function of effector immune cells in distant tumor foci ( 9 , 93 95 ). Therefore, anti-tumor responses outside the radiation field strengthened by low-dose RT were termed the “RadScopal effect” by them ( 9 , 96 ).…”
Section: Abscopal Effect Of Radiation Combined With Immunotherapymentioning
confidence: 99%
“…Nevertheless, other studies suggested different RT doses and segmentations played various immunomodulatory role ( 87 ). Some scholars considered low-dose RT, which is commonly used for patients with metastatic diseases as palliative care ( 91 , 92 ), can better induce anti-tumor immune activation at the molecular level, reshape TIME, and improve the infiltration and function of effector immune cells in distant tumor foci ( 9 , 93 95 ). Therefore, anti-tumor responses outside the radiation field strengthened by low-dose RT were termed the “RadScopal effect” by them ( 9 , 96 ).…”
Section: Abscopal Effect Of Radiation Combined With Immunotherapymentioning
confidence: 99%